The role of video conferencing in foreign language learning among young students - Medic, Branko (The journal of contemporary issues in business and government, 2021)
With advancements of technology and the rise of the Internet, an increasing number of educational organisations deliver courses online (Klibanov, et al., 2018). Even before the coronavirus pandemic in 2020, almost 20% of US students have taken one or more of their undergraduate modules remotely (National Center for Educational statistics, 2018). Along with wikis and blogs, video conferencing is a popular and well-established method for online education, as it has been around for more than 50 years (Roth, Pierce and Brewer, 2020). Then 2020 came, when remote education with video conferencing became “the basic global mode of course delivery”. So, “the quality of this delivery is essential” (Fatani, 2020, p. 1). This sharp shift provoked a personal interest in the impact that technology-assisted tutoring has and will increasingly have on young learners. Are they “digital natives” who embrace and prefer web-conferencing tools, or they would still opt for the traditional classroom? The research puzzle involves multiple educational and psychological aspects. When comparing video conferencing with traditional tutoring, there are inevitable differences in student’s attitudes, satisfaction, learning strategies and outcomes. It is personally intriguing to trace these effects, and reflect on the impact of technology on our personal and professional lives. From the perspective of foreign language professionals, understanding the effects that video conferencing has on youngsters is pivotal. It is the tutor’s role to facilitate the best possible learning outcomes by interacting with distant audiences, engaging and motivating them. During the COVID-19 pandemic most professionals had to move away from face-to-face teaching. However, teachers, just like everyone else, are reluctant to change. The majority reported resistance to web conferencing instruction, and only 9% of academics actually prefer teaching online (Educause, 2017). Much of these negative attitudes come from lack of knowledge and understanding. Therefore, for practitioners is of utmost importance to take a closer look at video conferencing tutoring, how it works and how it impacts young language learners.